Thermoelectric transport properties of PbTe-based composites incorporated with Cu2Se nano-inclusions. (11th January 2016) - Guo, Haifeng; Xin, Hongxing; Qin, Xiaoying; Jian, Zhang; Li, Di; Li, Yuanyue; Li, Cong
Abstract: Thermoelectric transport properties of Lead telluride (PbTe)-based composites incorporated with Cuprous selenide (Cu2 Se) nano-inclusions were investigated from 300 K to 800 K. Here, except for the transition from p-type to n-type conduction that occurs in pristine PbTe at ~530 K due to the difference of mobility between thermally electron and hole at high temperature, another transition from p-type to n-type conduction at 300 K with an increasing proportion of Cu2 Se could be due to the donor levels introduced by defects and unsaturated bonds at the interfaces. Moreover, by incorporating a small proportion (5 vol.%) of Cu2 Se nanoparticles into the PbTe matrix to form nano-composites, both a reduction (~55%) in lattice thermal conductivity and an enhanced electrical conductivity compared with that of pristine PbTe are obtained, which allows the thermoelectric power factor to reach a larger value (~11.2 μ W cm −1 K −2 ). Consequently, a maximum value ZT  =  0.91 is obtained at 760 K in the PbTe-5 vol.% Cu2 Se sample.